Norepinephrine Enhances Aerobic Glycolysis and May Act as a Predictive Factor for Immunotherapy in Gastric Cancer - Yangyang Wang; Shuchang Wang; Qin Yang; Jun Li; Fengrong Yu; Enhao Zhao (Journal of Immunology Research)
Objective/Background and Aims. The gastrointestinal tract is rich in neurotransmitters, which play an essential role in the occurrence and development of gastrointestinal tumors. We aimed to explore the function of neurotransmitters in gastric cancer and identify a suitable target to treat gastric cancer patients in the future. Methods. Monoamine neurotransmitters were detected in gastric cancer tissue and paired normal tissue, and The Cancer Genome Atlas was used to identify differentially expressed norepinephrine-degrading and synthetic enzymes. Quantitative real-time PCR and the Seahorse assay were used to determine the effect of norepinephrine on gastric cancer cell glycolysis. MAOA expression in cancer tissues was analyzed by immunohistochemistry and was compared with the patient SUVmax value of PET-CT and other clinicopathological characteristics. Results. The norepinephrine levels were markedly high in gastric cancer tissue, while the norepinephrine-degrading enzymes MAOA and MAOB showed low expression. High norepinephrine levels were associated with activated glycolysis. The MAOA or MAOB expression levels in tumor tissue were closely correlated with the patient SUV max values of PET-CT and immunotherapy evaluation indices, such as PD-L1 and the microsatellite status. Conclusions. Norepinephrine shows relatively higher expression in gastric cancer tissue than in normal tissue, and its expression level is associated with the glycolysis levels in patients. The norepinephrine-degrading enzymes MAOA and MAOB have significant expression differences in cancer and normal tissue, and their missing or low expression may predict immune therapy outcomes for gastric cancer patients. High norepinephrine levels with metabolic abnormalities may be more suitable for metabolic targeted therapy or immunotherapy.